Psychometric properties of the Spanish version of the hospital anxiety and depression scale in cancer patients - Vilela-Estrada, Ana L.; Villarreal-Zegarra, David; Copez-Lonzoy, Anthony; Esenarro-Valencia, Loida; Sánchez-Ramírez, José C.; Lamas-Delgado, Fernando; Ambrosio-Melgarejo, Juan; Reategui-Rivera, C. Mahony; Finkelstein, Joseph (Frontiers in Psychology, 2025)
BackgroundAlthough the Hospital Anxiety and Depression Scale (HADS) has been widely studied across various populations, there is still no consensus on its factor structure. This study aims to evaluate the psychometric properties of the HADS in cancer patients.MethodsOur study was cross-sectional and non-probabilistic. It involved 467 cancer patients aged 18 years and over, who were treated at a public institution specialized in oncology. The Hospital Anxiety and Depression Scale, the Beck Anxiety Inventory, and the Beck Depression Inventory were used. We evaluated their internal structure, measurement invariance, relationship with other variables, and reliability.ResultsIt was found that the HADS is best suited to a bifactorial structure where there is one general factor (emotional distress) and two specific factors (anxiety and depression). The HADS demonstrates invariance with respect to sex and years of education. It shows a moderate correlation with the Beck Anxiety Inventory and the Beck Depression Inventory. In addition, it presents acceptable levels of reliability and relationship with instruments used in the diagnosis of anxiety and depression.ConclusionThe HADS is best suited to a bifactorial structure in cancer populations, with comparisons across both sexes and varying levels of education. Its brevity, versatility, hospital-focused design, and extensive validation make the HADS a very important instrument in the detection of anxiety and depression in cancer patients.